Atributos químicos e microbiológicos de solos hidromórficos originados de basalto no sudoeste do Paraná - Viceli, Jéssica Maiara (2020)
Hydromorphic soils are located in places with surface water table and have functions to regulate water flow, recharge aquifers, natural corridors of native species and flora with typical species, therefore the protection and conservation of these soils is of fundamental importance. However, the lack of studies on ecological interactions, particularly the dynamics of edaphic attributes, hinder this process. The objective of the work was to evaluate chemical and microbiological attributes of hydromorphic soils in areas of permanent preservation (APP) originated in basalt in the Southwest of Paraná. The work was carried out in 2018 and 2019 in three areas of hydromorphic soils with different levels of water saturation and in a control area (well drained) in the municipality of Dois Vizinhos - PR. The soil was sampled (0-10 cm) in 08 points per area and in the four seasons of the year to verify the influence of humidity and temperature on chemical and microbiological parameters of the soil. In the soil with high water saturation (AS), the microbiological parameters respirometry, Cmic and qCO2 were higher in all evaluated seasons, mainly in the summer, the rainiest period that increased the saturation with water. This indicates unfavorable conditions for soil microorganisms, which also explains the higher MOS content. In the soils with medium (DM) and low saturation (BS) by water, in all periods evaluated, the qMIC was higher, indicating greater immobilization of organic carbon in the soil. They also showed greater oscillation of the microbiological attributes between the collections, due to the variation in the water saturation condition of the medium. On the other hand, the welldrained soil (BD) showed the lowest values of microbiological attributes, in addition to little oscillation throughout the year. The chemical parameters of the soil did not fluctuate between the seasons of the year for all evaluated areas. Soil with AS showed greater acidity and Al3 + content, while soils with MS and BS showed a higher content of P, Mg and Ca, indicating greater availability of nutrients, due to the fluctuation of the water table, which causes wetting and drying cycles. The BD soil showed less acidity, influenced by the lower MOS content. It is concluded that the hydromorphic soils have chemical and microbiological attributes different from those observed in well-drained soils in the Southwest of PR. Throughout the year, due to the variation in rainfall and temperature, the microbiological attributes of well-drained hydromorphic soils fluctuate while the chemical attributes remain stable.